Valmont [videorecording (DVD)] - Forman, Miloš; Firth, Colin, 1960-; Bening, Annette; Tilly, Meg; Balk, Fairuza; Phillips, Siân, 1933-; Jones, Jeffrey, 1947-; Thomas, Henry, 1971-; Laclos, Choderlos de, 1741-1803 (MGM Home Entertainment, 2002)
The vindictive widow Merteuil bets her friend debaucherous Valmont that he cannot seduce the virtuous (and married) Madame de Tourvel. If Valmont succeeds he may also bed Merteuil, but if he fails he must join a monastery. Set amongst the aristocracy in France in the 18th century.